KARAKTERISTIK MODUL PENYERAP ENERGI IMPAK MEKANISME INTERNAL INVERSION DAN AXIAL SPLITTING - Setiawan, Rachman; Amir, Muhammad Hisyam; Sugiharto, Bambang; Fajrianto, Sigit (Mesin, 2006)
The application of crashworthiness technology to a vehicle has a main objective of protecting the passenger or cargo from the effects of impact/collision. One of the strategies is by using impact energy absorbing (IEA) modules. Two of the alternatives of IEA modules are metallic tubes with internal inversion and controlled axial splitting mechanism. This paper presents both numerical and experimental approaches to understand the characteristics of the two mechanisms, before using them in design phase. LS-Dyna was used as the numerical simulation software for drop test case. The result of simulation is presented as the relationships between geometrical parameters and the crashworthiness parameters, e.g. impact energy and response force. Some cases are compared with quasi-static and drop test results.